Redesigning Maritime Port Ecosystems: Leveraging Blockchain for Transparent, Circular, and Sustainable Port Management - Weda, Iwan (IJESS International Journal of Education and Social Science, 2025)
The accelerating demands for environmental accountability, operational transparency, and resource efficiency have placed maritime ports at the center of a critical transition. Traditionally governed by linear logistics and fragmented governance structures, port ecosystems face increasing pressure to align with global sustainability targets such as the European Green Deal and the UN Sustainable Development Goals (SDGs). This paper introduces the Blockchain-enabled Circular Port Management (BCPM) framework—a novel, systems-based approach to digitally transform maritime port operations through blockchain technology. By embedding circular economy principles within blockchain-enabled data architectures, BCPM fosters transparency, trust, and lifecycle accountability across diverse port stakeholders. Drawing on a mixed-methods research design that includes case analysis, stakeholder interviews, and system modeling, the study demonstrates the empirical viability of the BCPM framework in enhancing material traceability, reducing transactional friction, and optimizing port circularity metrics. The findings offer both theoretical advancement and actionable guidance for port authorities, regulators, and supply chain actors seeking to operationalize sustainability through digital innovation. The paper concludes with a roadmap for implementation and identifies key areas for future research, including governance interoperability, real-time monitoring, and incentive alignment within port-centric blockchain ecosystems.